Pathogenesis, diagnosis and therapeutic strategies in WHIM syndrome immunodeficiency - Heusinkveld, Lauren E. (Expert Opin Orphan Drugs, 2017)
2.1 INTRODUCTION: WHIM syndrome is a rare combined primary immunodeficiency disorder caused by autosomal dominant gain-of-function mutations in the chemokine receptor CXCR4. It is the only Mendelian condition known to be caused by mutation of a chemokine or chemokine receptor. As such, it provides a scientific opportunity to understand chemokine-dependent immunoregulation in humans and a medical opportunity to develop mechanism-based treatment and cure strategies. 2.2 AREAS COVERED: This review covers the clinical features, genetics, immunopathogenesis and clinical management of WHIM syndrome. Clinical trials of targeted therapeutic agents and potential cure strategies are also included. 2.3 EXPERT OPINION: WHIM syndrome may be particularly amenable to mechanism-based therapeutics for three reasons: 1) CXCR4 has been validated as the molecular target in the disease by Mendelian genetics; 2) the biochemical abnormality is excessive CXCR4 signaling; and 3) antagonists selective for CXCR4 have been developed. Plerixafor is FDA-approved for hematopoietic stem cell (HSC) mobilization and has shown preliminary safety and efficacy in phase I clinical trials in WHIM syndrome. Gene editing may represent a viable cure strategy, since chromothriptic deletion of the disease allele in HSCs resulted in clinical cure of a patient and because CXCR4 haploinsufficiency enhances engraftment of transplanted HSCs in mice.